The CORRELATION OF ORAL HEALTH LITERACY AND GINGIVAL STATUS AMONG ELDERLY IN YOGYAKARTA: A CROSS-SECTIONAL STUDY - Rodestawati, Budi; Vega, Christia Aye Waindy; Nur'aini, Bekti; Widita, Elastria (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: The aging population is growing faster in several countries around the world, including Indonesia. Oral health literacy as a personal-behavioral component has been studied and is regarded an important determinant of health as well as a causative factor for oral health disorders, which are subsequently thought to have an impact on oral health-related quality of life. Objective: The purpose of this study was to investigate the association between oral health literacy and oral health status among elderly in Yogyakarta. Method: This cross-sectional study included 193 respondents aged ?60 years in Yogyakarta City. The data collection was done using interviewer-administered questionnaires (socio-demography data, health history, health behavior, and oral health literacy) and clinical examination. The Modified Gingival Index is used to determine gingival health status during a clinical examination of the oral cavity. Result: The results of this study indicated that there was a significant relationship between oral health literacy and Modified Gingival Index (p=0.01). Understanding participants' oral health literacy levels was critical for developing successful health education materials and intervention programs that enhance oral health. Conclusion: Elderly people with higher oral health literacy have better oral health outcomes.